PUITIKA POSTMODERNISME DALAM NOVEL KITAB OMONGKOSONG KARYA SENO GUMIRA AJIDARMA - , Ahmad Supena ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Various patterns of repertoire strategies that summon of ontological charactershad found.This ontological plurality has called poetic literary postmodernism. The background of this thesis is concerning the ontological character of the repertoire of summon strategies in poetic postmodernism. The primary data of this research is the novel of KitabOmongKosong(KOK) by Seno GumiraAjidarma, which published by PT BentangPustaka in 2006 in Yogyakarta totaling 524 pages.There is a plurality ontologism are grouped into several categories including: (1) the worlds, (2) construction, (3) the words, and (4) baseline in the novel of KitabOmongKosong by Seno GumiraAjidarma. A plurality of the worlds ontologism category contained the insertion zone development strategy, intertextuality zone and postmodernism fiction strategy, which had shown the interface between the worlds objects those are projected in a work of fiction. Furthermore, the construction category includes the worlds of China box.Whereas, in the sphere words to describe of the repertoire strategy character ontologism, with the sphere worlds of stylized. Then, describe the changes to the original works of fiction that emphasizes the unity of the discourse of fiction with a plurality of discourse puts forward the carnival.This story contain of Mahakalaand Sutasoma, story of Lubdhaka, story of sage Gotama and his children and the twin brother of KeboMilih and KeboNgraweng. Subsequently, the nature of ontological grounding summon discuss which is the result of the relationship of text, intertextual relations, between the worlds fictional. This section discusses the ontological summon character which is a result of the author's relationship with the text. The story in the novel turns KOK 2006 reception of the Ramayana. Author in the context of the speaker of the figures in the search for the author is not referring to the author of the novel, the SGA, which ends the novel identifies himself as Togog. As a reflection, the process of formation of the repertoire of strategies summon ontological nature of poetic postmodernism, it can only be through a poetic renaissance or heterokosmos view, the analogy between the author and God, and the theory of German romanticism. This is where true operations methodological poetic postmodernism is not closed and is not limited to space worlds, construction, word, and grounding.